VALUE OF RESISTANCE AND SYSTEM OF LIFE MEANINGS FOR PREVENTION OF PROFESSIONAL DEFORMATION OF TEACHERS AND PSYCHOLOGISTS - Berberyan, A.S. (Modern Psychology, 2019)
The article analyzes the issues of strengthening the psychosomatic health of specialists of “helping” professions in order to increase the effectiveness of their professional activities. The aim this survey is to study the significance of the features of resilience and the system of vital meanings for the psychosomatic health of teachers and psychologists in order to prevent them from professional deformation. The results of a practical research indicate that there are correlations between psychosomatic complaints, the level of anxiety, the level of neurotization and psychopathy, and the level of vitality of specialists. The analysis of the subjective perception of indicators of psychosomatic health and the system of life meanings showed that teachers and psychologists have a different system of life values. For the psycho-prophylactic of professional deformation, diagnosis, medical and psychological support of the specialist’s professional activity are needed
Keywords: professional deformation; psychosomatic health; vitality; life meanings